2019
DOI: 10.1371/journal.pone.0223804
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial resistance genotypes and phenotypes of Campylobacter jejuni isolated in Italy from humans, birds from wild and urban habitats, and poultry

Abstract: Campylobacter jejuni, a common foodborne zoonotic pathogen, causes gastroenteritis worldwide and is increasingly resistant to antibiotics. We aimed to investigate the antimicrobial resistance (AMR) genotypes of C. jejuni isolated from humans, poultry and birds from wild and urban Italian habitats to identify correlations between phenotypic and genotypic AMR in the isolates. Altogether, 644 C. jejuni isolates from humans (51), poultry (526) and wild- and urban-habitat birds (67) were analysed. The resistance ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
41
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 52 publications
21
41
3
1
Order By: Relevance
“…This may explain the dissimilarity in major resistance patterns among Campylobacter strains reported in different studies. For example, in contrast to the results obtained in this study a low frequency of erythromycin resistant strains but high frequency of resistance to ciprofloxacin, nalidixic acid and tetracycline were reported for Campylobacter isolates in Italy and Brazil [10,36]. The higher frequency of resistant strains in C. jejuni than C. coli, particularly when considering resistance to multiple antimicrobials, namely, amoxicillin, tetracycline, erythromycin and ciprofloxacin ( Table 2, and also see Additional file 4), could be related to the overwhelming natural predominance of the former species.…”
Section: Discussioncontrasting
confidence: 99%
“…This may explain the dissimilarity in major resistance patterns among Campylobacter strains reported in different studies. For example, in contrast to the results obtained in this study a low frequency of erythromycin resistant strains but high frequency of resistance to ciprofloxacin, nalidixic acid and tetracycline were reported for Campylobacter isolates in Italy and Brazil [10,36]. The higher frequency of resistant strains in C. jejuni than C. coli, particularly when considering resistance to multiple antimicrobials, namely, amoxicillin, tetracycline, erythromycin and ciprofloxacin ( Table 2, and also see Additional file 4), could be related to the overwhelming natural predominance of the former species.…”
Section: Discussioncontrasting
confidence: 99%
“…This may explain the dissimilarity in major resistance patterns among Campylobacter strains reported in different studies. For example, in contrast to the results obtained in this study a low frequency of erythromycin resistant strains but high frequency of resistance to ciprofloxacin, nalidixic acid and tetracycline were reported for Campylobacter isolates in Italy and Brazil [10,33]. The higher frequency of resistant strains in C. jejuni than C. coli, particularly when considering resistance to multiple antimicrobials, namely, amoxicillin, tetracycline, erythromycin and ciprofloxacin ( Table 2, and also see Additional File 4), could be related to the overwhelming natural predominance of the former species.…”
Section: Environmental Health and Hygiene Practicescontrasting
confidence: 99%
“…The gastrointestinal tract of poultry, wild birds, and livestock animals constitute the primary reservoir of Campylobacter spp. Campylobacter jejuni and Campylobacter coli are the predominant species of Campylobacter in poultry [5,10]. These bacteria are commonly known to be harmless gut flora of chicken, which remain healthy but serve as carriers for human infection.…”
Section: Introductionmentioning
confidence: 99%
“…isolated from humans. Elhadidy et al [30], found 49.7% resistance to tetracycline, much in accordance with the level of resistance found by Marotta et al [31], with 49.0% resistant isolates, even though this last study used the epidemiological cut-off values (ECOFFs) defined by EUCAST [32]. Considering the same resistance definition, the study carried out in Spain by Ocejo et al [33] showed that the level of resistance in Campylobacter spp., isolated from animals, was 76.5%.…”
Section: Discussionsupporting
confidence: 68%